ANALISIS STRUKTUR DAN KEBAHASAAN BERITA DALAM ACARA “RADAR MALAM” DI RADAR LAMPUNG TV - Sahala Aulia Siregar; Fransisca S.O. Dedi; Andri Wicaksono (LPPM STKIP PGRI Bandar Lampung, 2021)
The purpose of this study is: 1) to find out and describe the structure of the news contained in the delivery of news on the night radar program, and 2) to find out and describe the linguistic characteristics in the delivery of news on the night radar program. This research method uses descriptive qualitative. The data sources of this research are scripts and videos of the news event of Radar Malam Edition 5 October 2021. The data collection techniques used in this research are; documentation, observation and interview techniques. The results showed that the structure of the news contained in the Radar Malam program was complete and in accordance with predetermined indicators. The linguistic characteristics used in the news are in accordance with the linguistic characteristics of the news contained in the indicators to be analyzed.